Cultivating Sulla for Silvopastoral Restoration the Mediterranean Basin - Louhaichi, Mounir; Slim, Slim; Hassan, Sawsan; Verbist, Joren (Food and Agriculture Organization of the United Nations, 2023)
This innovative agricultural approach employs the drought-resistant native forage legume, Hedysarum coronarium (Sulla), to address the challenges faced by semi-arid regions in Tunisia. The strategy focuses on enhancing soil quality through soil cover, nitrogen fixation, biodiversity enhancement, and improved water infiltration. Additionally, Sulla contributes to improved fodder quality and availability, offering a sustainable solution for livestock grazing in areas prone to degradation. The collaboration between the International Centre of Agricultural Research in Dry Areas (ICARDA) and national partners has yielded positive impacts, demonstrating increased productivity, reduced erosion, and enhanced socio-economic resilience.